TEACHING ENGLISH TO YOUNG LEARNERS THROUGH SHORT STORIES: WHY AND HOW - Syilvia Wenny J (Universitas Muhammadiyah Muara Bungo, 2020)
Teaching English to young learners is not the same as teaching adults. Children are very active and imaginative but they tend to have short attention span. Teacher should create learning environment as interesting as possible to keep their spirit high during teaching and learning process. In line with this, short stories can be a bridge to facilitate them to learn English. Teacher can explore them to make English learning more interesting and effective. This media helps students to concentrate and engage more enthusiastically in learning English. This paper aims to investigate the value of using short stories and how it is applied in young learners’ classroom. It is hoped that this study is helpful for English teachers of young learners to gain more knowledge on how to create interesting learning environment for a successful learning process.